Diagnóstico da adoção de técnicas de produção enxuta na indústria de móveis de aço e sistemas armazenagem de Ponta Grossa - PR - Ferreira, Heitor Lopes (2010)
This dissertation is structured on the whole reality of management practices applied to existing production processes versus the concepts from the Toyota production system, now called lean production systems. The comparison made it possible to measure the degree of maturity in their current management systems and better understanding of what is practiced in day-to-day these companies. The bibliographic references sought to bring out the usual concepts of management with conventional theories that guide the process of lean production. Based on this depth, there is a need to contrast the information gathered during interviews with the existing reality on the factory floor that did not produced noises coming from ignorance or misunderstanding of the issues discussed. The survey was composed of three distinct phases. The first phase sought to allowing the bibliographic references to tease out the usual concepts of management with conventional theories that guide the process of lean production. The second phase sought through questionnaires, check how much managers know their companies and the level of knowledge they possessed concerning the techniques of lean production. The last phase focused onsite observation of the processes used in order to better understand the reality of each company as well as collecting subsidies for comparison with the responses from their managers. Recently there have been studies directed to these companies, however these studies focused on analyzing the competitiveness and governance system adopted by this cluster of companies, but in no case studies have been directed to strengthening the production systems processes adopted. The data collected have brought together the observations beyond graduation of maturity in its management processes of production, the spot verification of the sector has a shortage of methodologies that gives them better control over what happens on the factory floor. Faced with this shortage, the system of lean production comes as an alternative to the sector of production processes, using a holistic view proposed by the lean philosophy, translating all efforts on profitability, quality and satisfaction to all involved in the production process and its management systems.